Assessment of retinal nerve fiber layer thickness in myopic patients using optical coherence tomography - Ashraf S. Sharawy; Ahmed H. Aldghaimy; Osama AbdElmoneam El Soghair; Aya Mahmoud Badry (SVU - International Journal of Medical Sciences, 2019)
Background: Optical Coherence Tomography is the key tool for assessment of the retinal nerve fiber layer (RNFL) thickness which is occasionally altered in myopic patients. Aim of study: To assess the effect of different degrees of myopia on the thickness of retinal nerve fiber layer by the use of spectral domain optical coherence tomography . Patients and Method(s): Our study included examination of 40 myopic patients and 40 emmetropic persons.Retinal nerve fiber layer thickness was measured by the use of Optical Coherence Tomography. Results: Evaluation of RNFL thickness at the different sectors revealed that the thickness at the superior sector is of 102.13 ± 24.91μm for the myopics and of 124.5 ± 15.58 μm for the emmetropes. At the inferior sector the thickness was of 114.08 ± 25.15μm for the myopesanf of 134.63 ± 19.08 μm for the emmetropes ,at the nasal sector the thickness was of 71.9 ± 20.62 μm for the myopes and of 81.48 ± 9.45 μm for the emmetropes, at the temporal sector the thickness was of 75.25 ± 23.4 μm for the myopes and of 74.78 ± 13.42 μm for the emmetropes . Conclusion: Different grades of myopia affects the RNFL thickness by different degrees with the thinnest one goes to the high myopia. So, High myopia should be considered in the interpretation of OCT data because of thinning of RNFL thickness, and normative database corrected for refractive error and axial length should be incorporated.